3D reconstruction and flexibility of the hybrid engine Acetobacterium woodii F-ATP synthase - Kamariah, Neelagandan (2020)
The Na+-translocating F1FO ATP synthase from Acetobacterium woodii (AwF-ATP synthase) with a subunit stoichiometry of α3:β3:γ:δ:ε:a:b2:(c2/3)9:c1 represents an evolutionary path between ATP-synthases and vacuolar ATPases, by containing a heteromeric rotor c-ring, composed of subunits c1, c2 and c3, and an extra loop (γ195-211) within the rotary γ subunit. Here, the recombinant AwF-ATP synthase was subjected to negative stain electron microscopy and single particle analysis. The reference free 2D class averages revealed high flexibility of the enzyme, wherein the F1 and FO domains distinctively bended to adopt multiple conformations. Moreover, both the F1 and FO domains tilted relative to each other to a maximum extent of 28° and 30°, respectively. The first 3D reconstruction of the AwF-ATP synthase was determined which accommodates well the modelled structure of the AwF-ATP synthase as well as the γ195-211-loop. Molecular simulations of the enzyme underlined the bending features and flexibility observed in the electron micrographs, and enabled assessment of the dynamics of the extra γ195-211-loop.